ANALISIS KANDUNGAN KADMIUM (Cd) DAN TIMBAL (Pb) PADA AIR, SEDIMEN DAN KERANG BULU (Anadara antiquata) DI PERAIRAN PESISIR BELAWAN PROVINSI SUMATERA UTARA - Ruth Melisa; Mohammad Basyuni; Eko Budiyulianto (AQUACOASTMARINE, 2015)
Heavy metal pollution is one of the problems that often occur in coastal area. The coastal is a very important for fishing areas. Observations of heavy metal content in coastal waters Belawan was done in June − July 2014. The purpose of this study was to analyze the content of heavy metals Cd and Pb in water, sediment and Antique Ark (Anadara antiquata) at Belawan coastal waters. Determination station using purposive sampling method. Water quality measurements, including: pH, salinity, DO, temperature, brightness and depth. The results showed the water content of Pb in the range of 0,2 − 0,3 mg/l has been passed through the sea water quality standard that allowed 0,008 mg/l and the content of Cd in water < 0,006 mg/l. The content of Pb in the sediments from 16,1 − 25,6 mg/kg have not passed the quality standards set by the American (1995) and Chinese (2002) was equal to 450 mg/kg and 130 mg/kg respectively and the content of Cd in sediments < 0,006 mg/kg. Average heavy metal content of Antique Ark (Anadara antiquata) in the coastal waters of Belawan for (Pb: 3,6 − 5,6 mg/kg and Cd: 1,5 − 1,6 mg/kg), this value has passed the quality standard which has been established that for Pb: 1,5 mg/kg and Cd: 1,0 mg/kg respectively so it is not suitable for consumption.Keywords: Antique Ark, Heavy Metal, Coastal, Pollution, Cadmium, Lead